Effects of short-term inpatient treatment on sensitivity to a size contrast illusion in first-episode psychosis and multiple-episode schizophrenia - Silverstein, Steven M.; Keane, Brian P.; Wang, Yushi; Mikkilineni, Deepthi; Paterno, Danielle; Papathomas, Thomas V.; Feigenson, Keith (Frontiers in Psychology, 2013)
Introduction: In the Ebbinghaus illusion, a shape appears larger than its actual size when surrounded by small shapes and smaller than its actual size when surrounded by large shapes. Resistance to this illusion has been previously reported in schizophrenia, and linked to disorganized symptoms and poorer prognosis in cross-sectional studies. It is unclear, however, when in the course of illness this resistance first emerges or how it varies longitudinally with illness phase. Method: First-episode psychosis patients, multiple-episode schizophrenia patients and healthy controls completed a psychophysical task at two different time points, corresponding to hospital admission and discharge for patients. The task required judging the relative size of two circles centered on either side of the screen. Targets were presented without context (baseline), or were surrounded by shapes that made the size judgment harder or easier (misleading and helpful contexts, respectively). Context sensitivity was operationalized as improvement relative to baseline in the helpful condition minus the amount of decrement (relative to baseline) in the misleading condition. Results: At admission, context sensitivity was lower in the multiple-episode group than in the other groups, and was marginally less in the first episode than in the control group. In addition, schizophrenia patients were significantly more and less accurate than the other groups in the misleading and helpful conditions, respectively. At discharge, all groups exhibited similar context sensitivity. Poorer context sensitivity was related to higher levels of disorganized symptoms, and lower level of depression, excitement, and positive symptoms. Discussion: Resistance to the Ebbinghaus illusion, as a characteristic of the acute phase of schizophrenia, emerges after the first episode of psychosis. This suggests that visual context processing is a state-marker in schizophrenia and a biomarker of relapse and recovery.